PENGEMBANGAN INSTRUMEN DETEKSI DINI PERKEMBANGAN FISIK MOTORIK HALUS ANAK USIA EMPAT TAHUN - Yulia Isna Nursyifa, - (2022)
The background of this research is the lack of understanding of the Instrument for Early Detection of Fine Motor Physical Development for Four Years Old Children. The purpose of this study was to obtain information regarding the need for early detection instruments for fine motor physical development of children aged four years which was carried out at the PAUD level. Instrument for Early Detection of Fine Motor Physical Development of Four Years Old Children. And the feasibility of developing an Early Detection Instrument for Fine Motor Physical Development for Four Years Old Children. This study uses the EDR (Educational Design Research) model of the McKenney & Reeves model. In developing the instrument for early detection of fine motor physical development of children aged four years, researchers used the analysis and exploration stages; the design and construction stage (design and construction); and the evaluation and reflection phase; Maturing intervention and theoretical understanding. This research involved teachers and parents. data collection techniques through the distribution of questionnaire sheets. The final results of the study were obtained information about the basic needs of early detection instruments for fine motor physical development of children aged four years, the design of developing instruments for early detection of fine motor physical development of children aged four years, implementation of development of instruments for early detection of fine motor physical development of children aged four years, as well as the results of the development of an early detection instrument for the fine Motorik development of four-year-old children that can be used by teachers and parents. Penelitian ini dilatar belakang kurang pahamnya Instrumen Deteksi Dini Perkembangan Fisik Motorik Halus Anak Usia Empat Tahun. Tujuan dari penelitian ini yaitu untuk memperoleh informasi mengenai kebutuhan instrumen deteksi dini perkembangan fisik motorik halus anak usia empat tahun yang dilaksanakan di jenjang PAUD. Instrumen Deteksi Dini Perkembangan Fisik Motorik Halus Anak Usia Empat Tahun. Dan kelayakan dari pengembangan Instrumen Deteksi Dini Perkembangan Fisik Motorik Halus Anak Usia Empat Tahun. Penelitian ini menggunakan metode EDR (Educational Design Research) model McKenney & Reeves. Dalam pengembangan instrument deteksi dini perkembangan fisik motorik halus anak usia empat tahun peneliti menggunakan tahap analisis dan eksplorasi (analysis and exploration); tahap desain dan kontrusi (design and contruction); dan tahap evaluasi dan refleksi (evaluation and reflection); Maturing intervention dan theoretical understanding. Penelitian ini melibatkan guru dan orang tua. teknik pengumpulan data melalui penyebaran lembaran angket. Hasil akhir dari penelitian yaitu diperoleh informasi mengenai kebutuhan dasar instrumen deteksi dini perkembangan fisik motorik halus anak usia empat tahun, Desain pengembangan instrument deteksi dini perkembangan fisik motorik halus anak usia empat tahun, implementasi pengembangan instrument deteksi dini perkembangan fisik motorik halus anak usia empat tahun, serta hasil pengembangan instrument deteksi dini perkembangan fisik motorik halus anak usia empat tahun yang dapat digunakan oleh guru dan orang tua.